Hubungan Konsumsi Jenis MP-ASI dan Faktor Lain dengan Status Gizi Bayi Usia 6-12 Bulan (Studi di Wilayah Kerja Puskesmas Pandanarum Kabupaten Banjarnegara) - Haida Meytania Utami; Suyatno Suyatno; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat (Undip), 2018)
ABSTRACTNutritional status of infants aged 6-12 months is depending on complementary feeding because breast milk alone is not enough to meet the needs. The purpose of the research was to analyze the correlation of complementary feeding and other factors with nutritional status of baby aged 6-12 months in the working area of Padanarum Health Center Banjarnegara District. This was an observational analytic research with cross sectional design. Subjects were 31 baby boys and 29 baby girls, aged 6-12 months who were chosen using purposive sampling based on inclusion and exclusion criterias. Nutritional status was measured by weight scale and the Z-score was analyzed using WHO Anthro Plus. Food intake data was collected using food recall and processed using Nutrisurvey. Data was analyzed using Chi-Square, Rank Spearman and Pearson Product Moment Correlation test. The results showed that 11,67% respondents were malnutrition and 88,3% had normal nutrition, consumption of manufacturer complementary feeding was 20%, local was 28,3%, combination was 51,7%. Mother’s education <9 years was 33,3%, mothers were not working 70%, economy status was poor 22,3%. Level of energy less than RDA 43,3%, level of protein more than RDA 70%. Types of complementary feeding and level of protein was correlated with nutritional status of baby (p<0,05). Consuming manufacturer and local complementary food increase nutritional status of baby. Protein are important in baby’s growth. Level of mother’s education, mother’s knowledge, economy status, mother’s job, parenting and level of energy were not correlated with nutritional status of baby (p>0,05). It was recommended to consuming both manufacturer and local complmentary feeding for baby and add breastfeeding and infection to variable.